Alleviation of Depression by Glucagon-Like Peptide 1 Through the Regulation of Neuroinflammation, Neurotransmitters, Neurogenesis, and Synaptic Function - Kim, Young-Kook; Kim, Oh Yoen; Song, Juhyun (Frontiers in Pharmacology, 2020)
Depression has emerged as a major cause of mortality globally. Many studies have reported risk factors and mechanisms associated with depression, but it is as yet unclear how these findings can be applied to the treatment and prevention of this disorder. The onset and recurrence of depression have been linked to diverse metabolic factors, including hyperglycemia, dyslipidemia, and insulin resistance. Recent studies have suggested that depression is accompanied by memory loss as well as depressive mood. Thus, many researchers have highlighted the relationship between depressive behavior and metabolic alterations from various perspectives. Glucagon-like peptide-1 (GLP-1), which is secreted from gut cells and hindbrain areas, has been studied in metabolic diseases such as obesity and diabetes, and was shown to control glucose metabolism and insulin resistance. Recently, GLP-1 was highlighted as a regulator of diverse pathways, but its potential as the therapeutic target of depressive disorder was not described comprehensively. Therefore, in this review, we focused on the potential of GLP-1 modulation in depression.